Analisis Putusan Pengadilan Negeri Jombang Nomor:15PDT.G/2014/PN.JMB Tentang Peralihan Hak Atas Tanah Dengan Menggunakan Bilyet Giro - Hartatik, Hartatik; Puspitawati, Dhiana (Universitas Negeri Malang, 2019)
This paper aims to review the Court Decision Number: 15 / Pdt.G / 2014 / PN.JMB dated October 14, 2014, relating to the validity of the transfer of land rights by buying and selling through payment using Bilyet Giro, and analyzing the settlement of the transfer of land rights using Bilyet Giro according to customary law. The method used in this paper is normative research to find a solution to the problem of transferring land rights through buying and selling using Bilyet Giro to produce a new opinion, theory or concept as a prescription related to the problem. The results of the analysis in this paper show that the payment in full with the Bilyet Giro against the price agreed in the sale of land rights must be declared valid and valuable, both in terms of the Civil Code and the concept of customary law, and according to the provisions of customary law, cash payment with Bilyet Giro is sufficient for the transfer of land rights due to buying and selling.